A comparison of mutagenic PhIP and beneficial 8-C-(E-phenylethenyl)quercetin and 6-C-(E-phenylethenyl)quercetin formation under microwave and conventional heating. Issue 7 (28th June 2018) - Fan, Daming; Li, Lijie; Zhang, Nana; Zhao, Yueliang; Cheng, Ka-Wing; Yan, Bowen; Wang, Qian; Zhao, Jianxin; Wang, Mingfu; Zhang, Hao
Abstract : Microwave heating produced less genotoxic PhIP and more human beneficial 6- CEPQ and 8- CEPQ than conventional heating. Abstract : 2-Amino-1-methyl-6-phenylimidazo[4, 5- b ]pyridine (PhIP) is the most abundant mutagen/carcinogen produced in high temperature treated protein food. Quercetin has been shown to inhibit PhIP formation by trapping phenylacetaldehyde to form two human beneficial adducts 6- C -( E -phenylethenyl)quercetin (6- CEPQ ) and 8- C -( E -phenylethenyl)quercetin (8- CEPQ ). Here we studied the formation of PhIP as well as the phenylacetaldehyde-trapping ability of quercetin in microwave heating and conventional heating systems. LC-MS was applied for the comparison of PhIP formed in chemical models using microwave heating and conductive heating. Results showed that PhIP was produced time dependently under both heating conditions. Microwave heating produced a smaller amount of PhIP compared with conductive heating. Moreover, quercetin showed a more potent inhibitory effect on PhIP formation in microwave heating systems than in conductive heating models. The amount of 6- CEPQ and 8- CEPQ produced in chemical models and onion/beef soup using microwave heating was about 5 and 1.5 times more than using conductive heating, respectively. Our results demonstrate that microwave heating was a much safer and healthier thermal processing technology than conventional heating in terms of formation of less mutagenic PhIP and production of more human beneficial compounds 6- CEPQ and 8- CEPQ .